Association between chest computed tomography findings and respiratory adverse events in rheumatoid arthritis patients undergoing long‐term biological therapy. (8th November 2018) - Matsumoto, Takuya; Iwano, Shingo; Takahashi, Nobunori; Asai, Shuji; Watanabe, Tatsuo; Asai, Nobuyuki; Sobue, Yasumori; Ito, Satoru; Ishiguro, Naoki; Kojima, Toshihisa
Abstract: Objective: This study aimed to assess the association between chest computed tomography (CT) findings and incidence of respiratory adverse events (RAEs), and to detect risk factors for RAEs, in RA patients treated with long‐term biological therapy. Methods: Clinical and radiological data of 332 RA patients who were treated with biological disease‐modifying antirheumatic drugs were collected. CT data were assessed by an experienced radiologist. Patients were categorized into the interstitial lung disease (ILD) group (n = 29), airway disease (AD) group (n = 76), co‐existing ILD and AD (Co‐existing) group (n = 6), and the group without detectable change (WDC, n = 221) based on CT findings and scores. The incidence of RAEs was calculated for each group, and risk factors for RAEs from CT findings were explored. Results: We identified 41 RAEs, including acute onset or exacerbation of ILD (ILD events, n = 15), respiratory tract infection events (infection events, n = 21), and other events (n = 6). Cumulative incidences of ILD events were 20.2, 3.75, 47.2, and 1.94 (/1000 patient‐years: PY) in the ILD, AD, Co‐existing, and WDC groups, respectively, and those of infection events were 11.3, 17.6, 23.6, and 2.39 (/1000PY), respectively. Severity, as assessed by CT scores, was correlated with the incidence of RAEs. Risk factors for ILD events were reticular and honeycomb changes, and those for infection events were consolidation, bronchial wall thickening, bronchiectasis, bronchiolitis, air trapping, and atelectasis after adjusting for background factors. Conclusion: Our findings highlight particular CT findings that are associated with RAEs in RA patients undergoing long‐term biological therapy.